Axiology Amidst the Onslaught of 4.0 Media-Based Influence - Gunawan Adnan; Asyraf Hj. Ab. Rahman (Institut Agama Islam Negeri (IAIN) Salatiga, 2021)
Axiology is a discourse related to the value or usefulness of science. Science that is developed and controlled by humans should principally be able to provide positive values for human development and keep science and technology away from dehumanization. Axiology must be a guide in developing science because science and technology can develop with the support of human ambition which can be directed by negative and positive factors. Therefore, morality becomes a very important factor when a scientist develops his knowledge. The scientific way of thinking has achieved extraordinary developments in the current era of information technology 4.0., which is well-known as the internet of things. Not all societies are ready for this fundamental change, which not only leads to changes in thought, but also in relation to the culture of the community. Everything is based on technology. The industrial revolution 4.0 reflects a combination of digital and biological physical technology that is able to change humans in the fields of artificial intelligence, genetic engineering, big data and cloud computing, which all of which change the political, social and economic system. Many taboo matters such as extending age, designing babies, intelligent robots with feelings and development of information media technology lead to the negative side. For this reason, the problem of axiology is very important to be implemented, especially in the midst of the onslaught of technology that tends to be value-free in the current era.